Standardization and Cross Validation of Alloreactive IFNγ ELISPOT Assays Within the Clinical Trials in Organ Transplantation Consortium. Issue 7 (24th May 2013) - Ashoor, I.; Najafian, N.; Korin, Y.; Reed, E. F.; Mohanakumar, T.; Ikle, D.; Heeger, P. S.; Lin, M.
Abstract Emerging evidence indicates memory donor‐reactive T cells are detrimental to transplant outcome and that quantifying the frequency of IFNγ‐producing, donor‐reactive PBMCs by ELISPOT has potential utility as an immune monitoring tool. Nonetheless, differences in assay performance among laboratories limit the ability to compare results. In an effort to standardize assays, we prepared a panel of common cellular reagent standards, developed and cross validated a standard operating procedure (SOP) for alloreactive IFNγ ELISPOT assays in several research laboratories supported by the NIH‐funded Clinical Trials in Organ Transplantation (CTOT) Consortium. We demonstrate that strict adherence to the SOP and centralized data analysis results in high reproducibility with a coefficient of variance (CV) of ∼30%. This standardization of IFNγ ELISPOTassay will facilitate interpretation of data from multicenter transplantation research studies and provide the foundation for developing clinical laboratory testing strategies to guide therapeutic decision‐making in transplant patients.